Pengaruh Profitabilitas, Efisiensi Operasional, Kualitas Aset, dan Likuiditas Terhadap Tingkat Kecukupan Modal Pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Putri Utami; Abel Tasman (Jurnal Ecogen, 2020)
This study aims to examine the effect of profitability, operational efficiency, asset quality, and liquidity on the capital adequacy level of the banking sector which is listed on the Indonesia Stock Exchange. This type of research is classified as causative descriptive research. The sample of this study was 28 banking companies listed on the Indonesia Stock Exchange in 2016-2018 selected using the purposive sampling method. The type of data in this study is secondary data. Data were collected by documentation techniques and analyzed using multiple regression analysis methods. Analysis prerequisite tests conducted include normality test, heterokedasticity test, multicollinearity test, and autocorrelation test. The data collected is processed with SPSS version 26.0. The results showed that profitability has a significant positive effect on the level of capital adequacy, Operational efficiency has a positive and not significant effect on the level of capital adequacy, asset quality has a significant negative effect on the level of capital adequacy, and liquidity has a negative and insignificant effect on the level of capital adequacy in the sector banks which are listed on the Indonesia Stock Exchange.Keywords : profitability, operational efficiency, asset quality, liquidity